2015
DOI: 10.1128/jb.00046-15
|View full text |Cite
|
Sign up to set email alerts
|

An Escherichia coli Mutant That Makes Exceptionally Long Cells

Abstract: Although Escherichia coli is a very small (1-to 2-m) rod-shaped cell, here we describe an E. coli mutant that forms enormously long cells in rich media such as Luria broth, as long indeed as 750 m. These extremely elongated (eel) cells are as long as the longest bacteria known and have no internal subdivisions. They are metabolically competent, elongate rapidly, synthesize DNA, and distribute cell contents along this length. They lack only the ability to divide. The concentration of the essential cell division… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 29 publications
1
24
1
1
Order By: Relevance
“…However, the SOS response is subsequently silenced after attempted DNA repair (47,48). Other studies have observed that when FtsZ is downregulated or mutated in parent cells, cells can reach up to 750 μm in length and are still metabolically competent and will synthesize DNA (49). This preservation of functionality is also supported by our results as the longer SimCells could still produce mCherry (Figs.…”
Section: Proteomics Revealed Changes In Global Regulation Of Proteins Insupporting
confidence: 89%
“…However, the SOS response is subsequently silenced after attempted DNA repair (47,48). Other studies have observed that when FtsZ is downregulated or mutated in parent cells, cells can reach up to 750 μm in length and are still metabolically competent and will synthesize DNA (49). This preservation of functionality is also supported by our results as the longer SimCells could still produce mCherry (Figs.…”
Section: Proteomics Revealed Changes In Global Regulation Of Proteins Insupporting
confidence: 89%
“…Phage infection is much rarer; however, some ongoing infections are still visible. There is also an exceptionally long E. coli cell shown in Figure , which is only recently described …”
Section: Resultsmentioning
confidence: 70%
“…Similarly, qRT-PCR analysis of MSMEG_4712 and MSMEG_5779, genes involved in cell-wallrelated processes, and MSMEG_3112 and MSMEG_4963, genes involved in intermediary metabolism and respiration, correlated well with microarray data. We also selected the principal bacterial cell division gene, ftsZ, for qRT-PCR analysis, as downregulation of this gene is known to make bacterial cells elongated, even though microarray data showed no significant differences in its expression level (41). The qRT-PCR analysis showed that in the knockout strains, the levels of ftsZ were significantly downregulated (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since depletion of ftsZ has been linked to a filamentous phenotype in bacteria (41,47), and the ⌬rel Msm and ⌬dcpA strains exhibited the filamentous phenotype, we checked expression of the principal cell division control gene ftsZ. The qRT-PCR analysis showed that it was downregulated in both the knockout strains, thus explaining the filamentous phenotype shown by ⌬rel Msm and ⌬dcpA strains (see Fig.…”
Section: Discussionmentioning
confidence: 99%